Permintaan dan Struktur Pasar Industri Semen di Kabupaten Pesawaran Lampung - Muhidin Sirat; Sunarmo Sunarmo; M Husaini; Abdurahman Abdurahman; Heru Wahyudi (Studi Ilmu Manajemen dan Organisasi, 2022)
Purpose: This research aims to find demand and market structure for the cement trade industry in Gedong Tataan Subdistrict, Pesawaran District. Research Methodology: : The analytical method used in this research is quantitative with interviews,  questionnaires, literature study, and regression.  Result: Cement prices have a negative significant effect on cement demand, but product quality and consumer services have a positive significant effect on cement demand. The structure of the cement trading services market belongs to a monopolistic market. Limitations: The limitation of this study is using primary data Contribution: Some markets set prices according to the wishes of the actors themselves without following company rules, that is what causes some actors to discriminate. because it belongs to a monopolistic market, each company must implement a non-price policy. Meanwhile, from the performance aspect, it shows that the condition is very achieved. Therefore, there must be efforts from traders such as improvements in terms of products, prices, cleanliness of places and storage.